Use of spider webs as indicators of air quality assessment of Lahore City. (15th December 2017) - Tahir, Hafiz Muhammad; Aamir, Hammad; Nadeem, Junaid
Abstract: High level of heavy metal contaminants in air is known to cause serious health problems if remained unchecked for a long period of time. Anthropogenic activities such as vehicular emissions and number of industries are responsible for increasing the level of heavy metals. The aim of the present study was to biologically monitor the level of heavy metal contamination by spider webs. These sites were selected based on variable traffic volume and number of industries. Atomic absorption spectrometry (AAS) was used for the analysis of metal pollution content. The study determined that the level of heavy metals at the selected sampling sites were several folds higher than that at the control site and in previously reported literature. Pb was determined to be the most abundant heavy metal, while Thokar Niaz Baig was reported as the most contaminated site. These elevated levels of metal contaminants are associated with heavy traffic flow, number of industries and constructional activities in the respective areas.